BACTERIAL PNEUMONIA CHARACTERISTICS AS A COMPLICATION OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Banurea, Nia Imaniar; Simanjuntak, Lisdayanti; Tambunan, Vina P; Br Girsang, Indah Muliana; Meilani (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background:The management of respiratory diseases and infectious complications requires an integrative approach that connects community epidemiology, critical care risk stratification, functional interventions, and the management of multidrug-resistant pathogens. Objective: This literature review aims to critically synthesize four major scientific articles (published between 2023 and 2024) that document significant clinical phenomena in the post-pandemic era, predictors of critical mortality, functional ventilation adaptations, and the growing threat of antimicrobial resistance Methods: A systematic review was conducted by evaluating the methodologies, key findings, and limitations of four independent studies, including an epidemiological analysis from Shanghai (n = 494), a retrospective ICU cohort study from Turkey (n = 416), a rapid review on bulbar function, and a multivariable survival analysis of solid organ transplant recipients in the United States (n = 897). Results: The synthesis revealed that the post-COVID-19 immunity debt phenomenon contributed to a surge in pediatric respiratory infections accompanied by a high rate of macrolide resistance (80%). In the ICU setting, the C-reactive protein-to-albumin ratio (CAR) and neutrophil-to-lymphocyte ratio (NLR) were identified as significant predictors of mortality among patients with severe COPD complicated by pneumonia or sepsis. Optimization of non-invasive ventilation (NIV) through mouthpiece ventilation (MPV) was shown to improve respiratory-swallowing coordination disorders in patients with neuromuscular diseases. Meanwhile, bloodstream infections caused by carbapenem-resistant Enterobacterales (CRE-BSI) increased the mortality hazard ratio among transplant recipients by up to 2.85 times. Keywords: Mycoplasma pneumoniae; Chronic Obstructive Pulmonary Disease (COPD); Non-Invasive Ventilation; CRE Bloodstream Infection; Contemporary Thematic Anal ysi